Higher Education Stimulating Creative Enterprise - Ely, Philip; Campbell, Frances (University for the Creative Arts, 2011)
This report summarises the impact of the Creative Advantage development programme, funded by the Higher Education Funding Council of England and by University for the Creative Arts, Arts University College Bournemouth and the University of Winchester. The project delivered an estimated £1.2 million worth of support for the creative industries in Dorset, Hampshire and Surrey supporting over 2100 individuals between 2009-2011.